Gestión de la responsabilidad social universitaria : Caso Escuela de Ingeniería de Antioquia - EIA (2009)
ABSTRACT: The high education institutions in Colombia make themselves the right questions for answering to the social responsibility of universities: ¿are we preparing students for facing to the new relationships in society? ¿Are we educating professionals who think that technology is something isolated which is not their business? ¿are we educating in ethics so that our professionals behave as model citizens and help to build a free and fair society? ¿Our students are touched with the national reality, are they really involved or just spectators? In this way, the high education institutions find a problem: how to make true all this thought and how to evaluate the effects of traditional practices in social transformation and the development of regions and the country. In this paper it is proposed a definition for social responsibility of universities and some indicators as a first answer to this problem.